2020
DOI: 10.1111/imm.13242
|View full text |Cite
|
Sign up to set email alerts
|

New developments in our understanding of ankylosing spondylitis pathogenesis

Abstract: Summary Ankylosing spondylitis (AS) is a common immune‐mediated inflammatory arthritis with a strong genetic predisposition. We review recent data from genetic and animal studies highlighting the importance of Type 17 immune responses. Furthermore, the efficacy (or lack thereof) of different anti‐cytokine monoclonal antibodies has highlighted the diversity of Type 17 immune cells and cytokines critical to AS and related spondyloarthritis pathogenesis. Recent studies have strongly implicated the gut microbiome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 89 publications
1
52
0
1
Order By: Relevance
“…AS is a complex disease that involves many factors (6). For patients with AS, there is currently no complete cure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AS is a complex disease that involves many factors (6). For patients with AS, there is currently no complete cure.…”
Section: Discussionmentioning
confidence: 99%
“…It is only understood that genetic factors play major roles in AS pathogenesis (5). Besides, environmental, immune, metabolic, and other factors are also common causes of AS (6). Presently, AS cannot be completely cured.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, one AS patient's HLA-B*27 subtyping was negative, which suggests that other pathogenic agents may also be involved in the pathogenesis of AS, such as aminopeptidase gene, IL-23R, Type 17 immunity, intergenic regions and gut microbiom. [35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the pathogenesis of SpA, JAKs are involved in the signaling of key cytokines within the IL-23/IL-17 pathway, and Genome-wide association studies have found single nucleotide polymorphisms (SNPs) for IL23R, JAK2, and TYK2 in ankylosing spondylitis (AS) (11). IL-23, produced by activated myeloid cells, is important for the generation of IL-17 and IL-22 by target cells such as T helper cells 17 (Th17), gamma delta T cells (γδ T cells), or innate lymphoid cells (ILCs) type 3 (12). A combination of JAK2 and TYK2 transmits the IL-23 signal via STAT3 and, to a lesser extent, STAT4 (6,13).…”
Section: Janus Kinase and Signal Transducer And Activator Of Transcrimentioning
confidence: 99%